Japanese clinical practice guidelines for congenital biliary dilatation. (22nd January 2017) - Ishibashi, Hiroki; Shimada, Mitsuo; Kamisawa, Terumi; Fujii, Hideki; Hamada, Yoshinori; Kubota, Masayuki; Urushihara, Naoto; Endo, Itaru; Nio, Masaki; Taguchi, Tomoaki; Ando, Hisami; ,
Abstract: Until now, there have been no practical clinical guidelines for congenital biliary dilatation (CBD). In this review article, the Japanese Study Group on Congenital Biliary Dilatation (JSCBD) propose to establish clinical practice guidelines for CBD. Because the evidence‐based literature is relatively small, we decided to create guidelines based on the consensus of experts, using the medical literature for reference. A total of 20 clinical questions (CQs) were considered by the members of the editorial committee responsible for the guidelines. The CQs included the distinct aspects of CBD: (1) Concepts and Pathology (three CQs); (2) Diagnosis (six CQs); (3) Pancreaticobiliary Complications (three CQs); Treatments and Prognosis (eight CQs). Each statements and comments for CQs were made by the guidelines committee members. CQs were finally approved after review by members of the editorial committee and the guidelines evaluation board of CBD. These guidelines were created to provide assistance in the clinical practice of CBD management; their contents focus on clinical utility, and they include general information on CBD to make this disease more widely recognized.